Coach Rating Combined With Small-Sided Games Provides Further Insight Into Mental Toughness in Sport - Piggott, Ben; Müller, Sean; Chivers, Paola; Burgin, Matthew; Hoyne, Gerard (Frontiers in Psychology, 2019)
Literature indicates that mental toughness contributes to successful performance when faced with challenge. This study used an exemplar sport of Australian Rules football to investigate whether skilled performance thrived across increased challenge in small-sided games. Higher (n = 14) and lower (n = 17) skilled Australian footballers were recruited. First, coaches rated participants’ mental toughness (MTC) using the Mental Toughness Index. Second, participants competed in small-sided games where challenge was manipulated by varying the attacker to defender ratio to create lower and higher pressure scenarios. Decision-making, motor skill execution, and a combined total were measured. MTC rating was higher for higher skilled players. Total score of higher skilled players was significantly superior to lower skilled players in higher and lower pressure scenarios (p = .003 < .001 ). A ‘pressure differential score’, calculated to determine whether participants maintained performance across increased challenge, indicated a significant decrease in performance (total score) from lower to higher pressure scenarios for lower skilled (p = .011), but not for higher skilled (p = .060) players. Furthermore, MTC scores were predictive of associated with high pressure scenario total scores (p = .011). Findings suggest higher levels of mental toughness may contribute to maintain performance across the increased challenge of pressure within small-sided games. Practitioners can subjectively rate athlete mental toughness and then structure small-sided games to objectively measure performance under pressure scenarios. This provides an interdisciplinary approach to assess and train psychomotor skill.